Hubungan antara Rapid Naming dengan Kemampuan Pragmatik Anak Autism Spectrum Disorders - Ulil Azmi Al-Anshaary, M; Siswanto, Arif (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: Rapid naming allows someone to speak language well and correctly in social interactions. Language problems often occur in children with special needs, especially children with autism spectrum disorders. Objectives: To determine the relationship between rapid naming and the pragmatic abilities of children with autism spectrum disorders aged 3-8 years at PLDPI Surakarta. Methods: Descriptive correlational research design with a sample size of 30 people using total sampling. Results: Rapid naming is related to children's pragmatic abilities, because to be able to interact socially well, children must first master vocabulary and rapid naming. When a child's vocabulary increases and their rapid naming ability increases, the child is able to form phrases, these phrases will develop into sentences and then a series of sentences will form a story. The faster the duration produced, the better the child's rapid naming ability. Conclusion: The ability to analyze clients with rapid naming problems in children with autism spectrum disorders is apparently still lacking. There needs to be strategic steps from professional associations to be more precise in analyzing and implementing rapid naming of children with autism spectrum disorders. Keywords: Rapid Naming, Pragmatic, Autism Spectrum Disorders